Flow dynamics in stented ureter - Zheng, S; Carugo, D; Clavica, F; Mosayyebi, A; Waters, S (Springer, 2022)
Urinary flow is governed by the principles of fluid mechanics. Urodynamic studies have revealed the fundamental kinematics and dynamics of urinary flow in various physiological and pathological conditions, which are cornerstones for future development of diagnostic knowledge and innovative devices. There are three primary approaches to study the fluid mechanical characteristics of urinary flow: reduced order, computational, and experimental methods. Reduced-order methods exploit the disparate length scales inherent in the system to reveal the key dominant physics. Computational models can simulate fully three-dimensional, time-dependent flows in physiologically-inspired anatomical domains. Finally, experimental models provide an excellent counterpart to reduced and computational models by providing physical tests under various physiological and pathological conditions. While the interdisciplinary approaches to date have provided a wealth of insight into the fluid mechanical properties of the stented ureter, the next challenge is to develop new theoretical, computational and experimental models to capture the complex interplay between the fluid dynamics in stented ureters and biofilm/encrustation growth. Such studies will (1) enable identification of clinically relevant scenarios to improve patients’ treatment, and (2) provide physical guidelines for next-generation stent design.